Reductionism's Demise: Cold Comfort. - Wacome, Donald H. (Zygon: Journal of Religion & Science, 2004)
Nonreductive physicalism, as opposed to reductionism, enjoys wide popularity by virtue of being regarded as comporting with the traditional image of human beings as free and ontologically unique without the difficulties of mind-body dualism. A consideration of reasons, both good and bad, for which reductionism is rejected suggests instead that the move to nonreductive physicalism does nothing to mitigate the implications of a physicalist account of human nature.